2018
DOI: 10.1002/jrs.5332
|View full text |Cite
|
Sign up to set email alerts
|

Spin–phonon coupling in HoCr1 − xFexO3 (x = 0 and 0.5) compounds

Abstract: We report on the temperature dependent Raman scattering studies of polycrystalline HoCr1 − xFexO3 (x = 0 and 0.5) compounds. No signature of phonon mode related to structural phase transition is evident in the investigated temperature range in both the compounds. The thermal evolution of phonon spectra indicates a deviation of B3g(3) mode from the expected anharmonic behaviour below magnetic ordering temperature TN in HoCrO3 compound. This behaviour is attributed to spin–phonon coupling, which is due to the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The changes in phonon lifetime also suggest the presence of disorder in the compounds due to magnetic order. This type of disorder can be influenced near magnetic ordering due to titling or rotation of octahedral, ordering of Fe/Cr ions in oxygen octahedral or due to displacement of the rare-earth ion [46]. Additionally, from Figs.…”
Section: Raman Spectroscopic Studiesmentioning
confidence: 99%
“…The changes in phonon lifetime also suggest the presence of disorder in the compounds due to magnetic order. This type of disorder can be influenced near magnetic ordering due to titling or rotation of octahedral, ordering of Fe/Cr ions in oxygen octahedral or due to displacement of the rare-earth ion [46]. Additionally, from Figs.…”
Section: Raman Spectroscopic Studiesmentioning
confidence: 99%
“…The value of ∆ω 0 is 79 cm −1 and 44 cm −1 for (111) and (100) oriented CFMO films, respectively (table 4). Literature reports suggest that the higher value of ∆ω 0 implies higher spin-phonon coupling strength in the system [33]. Thus, the temperature-dependent Raman data suggest that the CFMO (111) films with higher cation ordering exhibit stronger spin-phonon coupling with higher ∆ω 0 .…”
Section: Vibrational Propertiesmentioning
confidence: 87%
“…The temperature-induced thermal expansion of the lattice produces red-shift of the Raman modes as expected. For a magnetic material, the red-shift of Raman modes can be attributed to various factors such as [24,32,33]: ω (T) = ω 0 + ∆ω ph−ph + ∆ω sp−ph + ∆ω anharmonic (7) where ω 0 is the Raman shift corresponding to 0 K, ∆ω ph-ph is the cell volume contribution, ∆ω sp-ph is the spin-phonon coupling contribution and ∆ω anharmonic signifies the contribution of anharmonic terms in the system. Here, ∆ω sp-ph arises because of modulation of spin exchange integral by a change in the lattice vibrational frequencies and hence signifies contribution from spin-phonon interactions.…”
Section: Vibrational Propertiesmentioning
confidence: 99%
“…[161] Kotnana investigated spin-phonon coupling in HoCr 1−x Fe x O 3 (x = 0 and 0.5) compounds. [162] Koyanagi and coworkers reported a correlation among Raman spectra, swelling, and irradiation temperature in the Raman spectra of neutron irradiated silicon carbide. [163] Premila et al performed Raman spectroscopic studies across the ferroelectric transition in cobalt substituted dimethyl amine manganese formate.…”
Section: Metals Carbons and Other Crystalline Materialsmentioning
confidence: 99%
“…They found that a numerous assemblage of organic inclusions is a diagnostic feature for gem quality green apatite from Anemzi . Kotnana investigated spin–phonon coupling in HoCr 1−x Fe x O 3 (x = 0 and 0.5) compounds . Koyanagi and co‐workers reported a correlation among Raman spectra, swelling, and irradiation temperature in the Raman spectra of neutron irradiated silicon carbide .…”
Section: Solid‐state Studiesmentioning
confidence: 99%